Learning oral presentation in a collaborative environment in tertiary classrooms: Islamic perspectives / Juritah Misman and Mardziah Hayati Abdullah - Misman, Juritah; Abdullah, Mardziah Hayati (2015)
Effective oral communication skills are very important for humans to proliferate positive and virtuous knowledge and information to others. Islam proposes good teaching and learning practices that help increase better learning environments. Commonly, oral presentation skills in tertiary English classrooms include approaches such as lectures of theories, usage of multimedia aids to teach students delivery skills and techniques to become effective speakers. The main aim of this study is to look at ways for students to learn oral presentation skills in a collaborative environment. The use of pair work activities are presented as means to help and support the learning of presentation skills through collaborative approaches which are creative and innovative. Four pairs of expert and moderate learners learned together in active learning activities which required them to make engaging discussions , give honest comments and feedback and give positive suggestions to help them become better speakers. Technology (such as notes, computers, cameras, videos) was also incorporated to aid learners in building and improving their presentation skills. The study also discusses Islamic perspectives towards collaborative learning environment of developing oral communication skills.